The End of the Printed Scholarly Monograph: Collapsing Markets and New Models - Barclay, Donald A (International Higher Education, 2016)
The printed scholarly monograph has been the bulwark of long-form scholarship for decades. Especially in the humanities and interpretive social sciences, the print-format scholarly monograph serves not only as the most highly regarded form of scholarly communication, but also as the ultimate measure of a scholar’s worth. However, the economic model supporting the publication of printed scholarly monographs is on the verge of collapse as financially hard-pressed academic libraries cannot afford to purchase printed volumes at anywhere near historical rates. While this could be seen as a disaster for long-form scholarship, a transition to open-access publication models will not only create larger audiences for book-length scholarly publications, it will also enhance long-form scholarship by accommodating the use of digital technologies that cannot be accommodated by the printed page.